A Review of Soil Organic Carbon in Ethiopia's Major Land Use Types (Applied Research in Science and Technology, 2022)
The carbon in soils related to the products of living organisms is noted as "soil organic carbon" (SOC). Soil is the largest terrestrial carbon sink, containing 2 to 3 times more carbon than the atmosphere and plants, respectively. The objective of this review is to assess and quantify SOC in Ethiopia across main land-use categories, as well as to identify critical gaps and priorities in SOC research and development. The existing literature search using research gateways, Google Scholar, and associated published and unpublished sources was employed as the methodological technique for this review. Previous authors have attempted to analyze and synthesize research on SOC in Ethiopia under major land use types emphasizing on the selected parts of the region. This is a key gap that this review aims to solve. According to the assessment, anthropogenic activities have nearly depleted 45 percent of the country's total landmass at this time. Forest Land (FL) > Grazing Land (GL) > (Cultivated Land) CL was the variable pattern for SOC. The highest SOC content was found in the FL, whereas the lowest was found in the CL. As a result of this analysis and research findings, it can be concluded that minimizing C losses by restoration of vegetation on degraded lands will improve SOC storage in Ethiopia, benefiting farmers and mitigating the current climate change.